2020
DOI: 10.3389/fimmu.2020.570083
|View full text |Cite
|
Sign up to set email alerts
|

The Challenge by Multiple Environmental and Biological Factors Induce Inflammation in Aging: Their Role in the Promotion of Chronic Disease

Abstract: The aging process is driven by multiple mechanisms that lead to changes in energy production, oxidative stress, homeostatic dysregulation and eventually to loss of functionality and increased disease susceptibility. Most aged individuals develop chronic low-grade inflammation, which is an important risk factor for morbidity, physical and cognitive impairment, frailty, and death. At any age, chronic inflammatory diseases are major causes of morbimortality, affecting up to 5–8% of the population of industrialize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 297 publications
(304 reference statements)
0
39
0
Order By: Relevance
“…Given the close association between oxidative stress and inflammaging [ 461 ] [ 461 , 462 ], targeting detrimental ROS at the production stage without affecting ROS signaling may improve immune function and ameliorate neuroinflammation [ 463 ]. Mitochondria-targeted antioxidants potently sequester reactive oxygen intermediates (ROIs) and confer greater protection against oxidative damage in the mitochondria than untargeted cellular antioxidants [ 464 , 465 ].…”
Section: Possible Intervention For Neuroinflammation In Admentioning
confidence: 99%
“…Given the close association between oxidative stress and inflammaging [ 461 ] [ 461 , 462 ], targeting detrimental ROS at the production stage without affecting ROS signaling may improve immune function and ameliorate neuroinflammation [ 463 ]. Mitochondria-targeted antioxidants potently sequester reactive oxygen intermediates (ROIs) and confer greater protection against oxidative damage in the mitochondria than untargeted cellular antioxidants [ 464 , 465 ].…”
Section: Possible Intervention For Neuroinflammation In Admentioning
confidence: 99%
“…Of note, a recent paper revealed that aging and obesity similarly impair antibody responses (11). Interestingly, in older age, the intrinsic functional impairment of immune competence and the lack of proper immune defense are associated with a low-grade chronic systemic inflammation (12), that may be attenuated by regular physical exercises (13,14), which are also common points with the immunological characteristics of obesity (15). Of note, studies in recent years have shown that obesity and insufficient physical activity have become a global health problem, and physical inactivity is the 4th most important risk factor for global mortality (16).…”
Section: Introductionmentioning
confidence: 99%
“…The predominant risk factor for neurodegenerative disease is age, and thus, represents a significant co-morbidity. Thus, understanding age-related changes in brain immune cells and the impact of those changes is critical in addressing the contributory role of these cells and processes to any neurodegenerative disease process [219][220][221][222]. A common feature of aging is "inflammaging" [223].…”
Section: Aging As a Co-factor For Neurodegeneration And Microgliamentioning
confidence: 99%